The Influence of E-Wallet Usability and Financial Literacy on Generation Z’s Consumption Behavior in Cirebon City - Nailah Hayatunnasha; Nurhana Dhea Parlina (Asian Journal of Management Analytics, 2026)
This study aims to analyze the influence of e-wallet usability and financial literacy on the consumption behavior of Generation Z in Cirebon City. The study employs a quantitative approach using an associative method and Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis. Data were collected via a questionnaire distributed to 246 Generation Z respondents who use e-wallets, using a 1–5 Likert scale. The results indicate that the ease of using e-wallets has a positive and significant effect on consumption behavior, suggesting that the easier digital payment systems are to use, the higher the tendency for individuals to make impulsive purchases. Meanwhile, financial literacy has a negative but insignificant effect on consumptive behavior, suggesting that financial understanding is not yet fully capable of controlling consumption behavior in the context of digital technology’s ease of use.